Influence of Social Media Marketing Instagram and Brand Awareness on Purchase Decisions of PT. Mepro's Products - Devi Natali Setiawati; Tongam Sirait (Riviera Publishing, 2024)
Social media platforms have become crucial tools in modern marketing strategies, significantly influencing consumer behavior and purchasing decisions. Instagram, with its visual-centric approach, has proven particularly effective in engaging users and building brand awareness. This study explores the impact of Instagram social media marketing and brand awareness on purchasing decisions of PT. Mepro products. This causal explanatory research employs both primary and secondary data collection methods. Primary data was gathered through questionnaires distributed to a minimum of 99 respondents, calculated using the Slovin method, who are followers of the mepro.official Instagram account and range in age from 11 to 68 years. Secondary data was obtained through literature review and analysis of historical data. Utilizing quantitative data and analyzed with SPSS 28, the research investigates the relationships between the independent variables—Instagram social media marketing (X1) and brand awareness (X2) and the dependent variable, purchasing decisions (Y). The findings reveal that both Instagram social media marketing and brand awareness significantly influence purchasing decisions, accounting for 59.6% of the variance, with other variables explaining the remaining influence. This research underscores the importance of strategic social media engagement and brand visibility in driving consumer purchases.